Implementasi Metode MD2 Untuk Autentikasi Hasil Citra Rontgen (Ronsen) - Harahap, Mahanum (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Implementation is considered as the main form and a crucial stage in the policy-making process or the implementation of a carefully and detailed plan, that without effective implementation, policy decisions will not be successfully executed. Implementation can also be interpreted as a series of actions carried out by various policy implementers with supporting means based on established rules to achieve predetermined goals. Authentication can also be interpreted as a very important thing in delivering information, both in the form of data or text messages. This is because authentication is needed for the authenticity of the contents of the data, with the existence of authentication, the use of authentication systems is expected to form a specific system in that field, one example is the implementation of X-ray image results where the authenticity of the data must be truly real with the results diagnosed by the doctor on the patient. The Message Digest Algorithm 2 (MD2) method can be interpreted as a cryptographic hash function developed by Ron Rivest in 1989, this algorithm is optimized using an 8-bit computer. MD2 is actually specified in RFC 1319 and the MD2 algorithm produces a hash value that is 18 bits in size and accepts input messages with an unspecified length. With this method, it is expected to solve problems that often occur in X-ray results so that the process of applying X-ray image results with doctor's diagnosis is tested for its authenticity value based on the MD2 method, then an application is built using the